Verruciform xanthoma located in anterior gingival - Hatakeyama, Márcia [UNESP]; Alonso, Juliana M.S.L. [UNESP]; Guilhermino, Marinaldo [UNESP]; Brandão, Adriana A.H. [UNESP]; Cavalcante, Ana Sueli R. [UNESP] (Medicina Oral, S.L., 2010)
Verruciform xanthoma (VX) is a relatively rare benign lesion and oral predominantly, which occasionally affects skin and genital mucosa. It appears as a papule or single plaque showing a verrucous or papillomatous aspect, with variable color from reddish pink to gray. In majority of oral cases, it affects gingiva and alveolar mucosa such a solitary lesion. Histopathological findings are foamy histiocytes within elongated dermal papillae. Treatment consists of conservative excision surgery and recurrence is rare. A clinical case is reported, located in anterior gingiva, showing good prognosis, without recurrence. There was no concomitant oral lesion associated. Local trauma was the only possibility suggested to be related to etiology. No relevant alterations in laboratory exams (hemogram, total cholesterol, HDL, LDL, VLDL, glycose and glycolized hemoglobin) were found. The origin of the lesion remains unclear and investigation for possible associations with other lesions that could present greater risk of carcinogenesis is required. © Medicina Oral S.L.
Keywords: Foam cells; Mouth; Xanthomatosis